Sociology noir: studies at the University of Chicago in loneliness, marginality, and deviance, 1915 - 1935 - Salerno, Roger A. (McFarland & Co. Inc., Publishers, 2007)
"Between 1915 and 1935 the University of Chicago was the center for the production of innovative sociological research that resonated with the lives of urban Americans. These studies focused on delinquents, prostitutes, gangsters, and homeless men. This work offers a survey of some key monographs such as The Unadjusted Girl, The Jack Roller, and The Taxi Dancer"--Provided by publisher